Does bilateral trade in cereals within SADC reflect virtual trade in water between countries with different water endowments? - Matchaya, Greenwell C.; Garcia, R. J.; Traoré, Fousseini (Informa UK Limited, 2023)
This paper examines intraregional bilateral trade in virtual water embedded in cereal flows between the Southern Africa Development Community (SADC) states. A gravity model is employed to examine whether annual bilateral trade depends on differences in water endowments, but also includes socio-economic and political determinants that affect trade. There is evidence that the abundance of water resources in a country influences trade for a product that is water dependent. Thus, the adverse effect of water scarcity in a country may be ameliorated by encouraging exports of water-intensive cereal crops where water is in abundance and imported where water is scarce.